High quality biodiesel and its diesel engine application: a review - Atadashi, I.M.; Aroua, Mohamed Kheireddine; Abdul Raman, Abdul Aziz (Elsevier, 2010)
The continuous increasing demand for energy and the diminishing tendency of petroleum resources has led to the search for alternative renewable and sustainable fuel. Biodiesel is best substitute for petro-diesel and also most advantageous over petro-diesel for its environmental friendliness. The quality of biodiesel fuel was found to be significant for its successful use on compression ignition engines and subsequent replacement of non-renewable fossil fuels. Conventional biodiesel separation and purification technologies were noticed to yield lower quality biodiesel fuel with resultant excessive energy and water consumptions. Membrane technology showed more potential for effective and efficient separation and purification of biodiesel. This technology need be explored for the attainment of better quality biodiesel fuels. This paper reviews the technologies used for the biodiesel separation and purification, biodiesel quality, and its effects on diesel engines. Biodiesel biodegradability, lubricity, stability, economic importance, and gaseous emissions have been discussed. (C) 2010 Elsevier Ltd. All rights reserved.